Zones of Terrestrial Coastal Issues and Development Communication Strategy in Padang Pariaman Regency - Nur, Hamdi; Wardi, Yunia; Evanita, Susi (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
This research aims to explore distinctive zones of terrestrial coastal issues in Padang Pariaman Regency and identify communication strategies to address each zone. This research employs a literature research method by collecting secondary data and interpreting, integrating, and analyzing information. This research identifies five zones for coastal management, namely a) sandy beach zone used for shrimp pond operations, b) sandy beach for recreation activity, c) coastal abrasion-prone zones, d) mangrove conservation zone, and e) sea turtle conservation zone. The government needs to empower and transform the community regarding knowledge, attitude, and practice through the development communication strategy. The important aspect of knowledge is information about coastal setback regulation and ecosystem processes with various impacts. Communication strategy for changing the attitude of people focused on avoiding causing harm to mangrove and turtle habitats and changing the habit of littering on the beach. Communities also have to be involved further in conserving mangroves and turtles.